Anticulture 2 : Drêve, une galerie d'art de 1 kilomètre de long - Rabineau, Agnès; Baras, Jean-Pol; Delwart, Michel; de Wasseige, Alain; Lemonnier, Arlette; Mariemont (Bruxelles : [s.n.], 1987)
Alexandre, Marc ; Bertleff, Philippe ; Biet, Alain ; Bijl, Guillaume ; Braeckman, Dirk ; Daems, Walter ; Debroux, Hedwige ; Decq, Bart ; Duchateau, Hugo ; Gasparotto, Paolo ; Lambrecht, Bernadette ; Lizene, Jacques ; Mulkers, Urbain ; Navez, Jean-Marc ; et al.
Drêve de Mariemont, 28 mai - 8 juin 1987
kunstcatalogus